2022
DOI: 10.36448/bl.v5i1.2649
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception in Learning Extensive Listening by Using Cartoon Movies

Abstract: Extensive listening is a way to practice listening skill thoroughly. Listening to various recordings, videos, and interviews on the same topic will help to get context in a real situation, and will help to learn more vocabulary. The objective of this research was to find out students' perceptions in learning extensive listening by using cartoon movies. This study used a qualitative method. The research was done at SMK Trisakti Jaya Bandar Lampung for the 10th grade students (N=38). Data gathering was done by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
4
3
0
Order By: Relevance
“…Both freshmen and juniors in this study largely concurred that learning English through movies could make them feel more excited than traditional learning methods and that it would be an effective way to enhance their language skills. These findings are indeed in line with the previous studies which indicated that English movies could aid learners in developing their language competencies (Andriani & Angelina, 2020;Larasati et al, 2021;Susanto et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Both freshmen and juniors in this study largely concurred that learning English through movies could make them feel more excited than traditional learning methods and that it would be an effective way to enhance their language skills. These findings are indeed in line with the previous studies which indicated that English movies could aid learners in developing their language competencies (Andriani & Angelina, 2020;Larasati et al, 2021;Susanto et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…First, the results achieved from the statistical analysis of the questionnaire showed that all the participants, both first-year and third-year English-majored students, had strong agreement with the positive impacts of watching English movies on their learning motivation as well as on their language development. These research findings are in accord with the previous studies (Andriani & Angelina, 2020;Larasati et al, 2021;Susanto et al, 2022) which stressed the significance of English movies in promoting the learners' language competence and proficiency.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations